How to make bibliographic references for research papers - Calero Vega, Gema Belén (Pulso. Revista de educación, 2001)
This article presents guidelines for creating bibliographies and citing sources, with a focus on electronic sources. It begins by explaining some fundamental concepts related to standardisation.